The metamorphosis of leadership in a democratic Mexico - Camp, Roderic A. (New York ; Oxford : Oxford University Press, 2011)
This title is a broad analysis of Mexico's changing leadership over the past eight decades, stretching from its pre-democratic era (1935-1988), to its democratic transition (1988-2000) to its democratic period (2000-the present).
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Political leadership -- Mexico; Democracy -- Mexico; Mexico -- Politics and government -- 1946-1970.; Mexico -- Politics and government -- 1970-1988.; Mexico -- Politics and government -- 1988-2000.